Odpowiedzi

2009-11-27T15:02:23+01:00
A) (x-y)-(z-v) = x-y-z+v
b) -(x+y)-(-z-v) = -x-y+z+v
c) -(x-y)+(z-v) = -x+y+z-v
d) -(-x+y)-(z-v) = x-y-z+v
e ) -(-x+y)+(-z+v) = x-y-z+v
f) -(-x+y) - (-z+v) = x-y+z-v

odp: a,d,e
23 4 23
2009-11-27T15:03:13+01:00
A) x-y-z+v
b)-x-y+z+v
c)-x+y+z-v
d) x-y-z+v
e)x-y-z+v
f)x-y+z-v
a,d,e
7 4 7
2009-11-27T15:04:46+01:00
A) (x - y) - (z - v) = x - y - z + v

b) - (x + y) - (-z - v) = - x - y + z + v

c) - (x - y) + (z - v) = - x + y + z + v

d) - (-x + y) - (z-v) = x - y - z + v

e ) - (-x + y) + (-z + v) = x - y - z + v

f) - (-x + y) - (- z + v) = x - y + z - v

Będa to wyrażenia: a, d, e.

Pozdro))
13 4 13